Pilot Projects of The University of Maribor for A Green and Resilient Transition to Society 5.0 - Tekavc, Joanna; Presker, Robert (Journal of Sustainability Perspectives, 2023)
In 2022, the University of Maribor has successfully acquired 23 pilot projects for a green and resilient transition to Society 5.0 as part of the Recovery and Resilience Plan of the Republic of Slovenia, which will be implemented in the period 2022-25. The aim of the pilot projects is thus to achieve curricular renewal and changes for a green, resilient, sustainable, and digitally connected university. We strive for sustainable, socially responsible, and high-quality development of scientific sciences and artistic disciplines as well as research fields and subfields developed by UM, considering the principles of smart specialization with an emphasis on solving social challenges. The pilot projects of the University of Maribor thus relate to the reduction of the mismatch between the knowledge of graduates and the needs of the labor market, as they address the harmonization of expectations regarding the knowledge of graduates on the part of the labor market and future professions on the one hand, and the creation of competences that the graduate should acquire through higher education studies on the other side. In this way, the study programs will be coordinated with the needs of the economy and society, and in addition to the competences dictated by the labor market, they will also acquire digital knowledge and competences for the green transition. With the planned contents of the pilot projects, we are thus linked to the sustainable development goals of the United Nations, which call on all learners to acquire the knowledge and skills necessary to promote sustainable development by 2030, also by including environmental and climate issues in higher education, which while simultaneously using digital technologies as additional powerful enablers of the green transition, promote sustainable behavior in the development and use of digital solutions. Recognizing that universities are the key stakeholders in dealing with major social challenges, in the proposed pilot projects we fully address the objectives of the Guidelines for the renewal of higher education professional education with the proposal of an implementation plan, namely the green transition, the digital transition and the area of lifelong education and micro-evidence.